STUDI KOMPARASI AKHLAK SISWA BOARDING SCHOOL DAN NON BOARDING SCHOOL DI SMA AL-MA'SOEM SUMEDANG - Kardiyah, - (2015)
This research was conducted because a problem that students character tend to be negative even bad. This happy because of liberalism factor, his factor influences students' style, it can be seen that hedonism of students attitude are often not suitable with the rules of religion and country, but other aspect Islamic School always had spread fast. This research aims to analyze the differences betwen student's character of Boarding School and students character of non Boarding School in the Senior High School of Al-Ma'soem. Descriptive method is used this study with quantitatif approach which has two free variable comparative design bind data was taken by one step group sample Cluster Randong Sampling, while there are two kinds of processing data the first is the analyze of inferensial data by using Microsoft Excel and Sofwere SPSS 20. According to all of character aspects in this study such as character toward self students, Character toward their parents and family, Character toward other people around them. So, the result of this study is the student's Character betwen Boarding School and non Boarding School by using chi quadrat formula average 0,107. If it can be seen at tabel quadrat of significance category avarage 5% or 5,991 so the value of chi quadarat in this study is more little such as 0,107 < 5,991. From the result the conclusion of this study that there is no difference significant teh students' character betwen Boarding school and non Boarding School. Keywords: Comparation, Character, Boarding, Non Boarding Penelitian ini dilatarbelakangi oleh problematika Akhlak siswa yang semakin krusial, serbuan arus liberalisme yang tidak terbendung seolah mempengaruhi 'style' di kalangan remaja, sikap hedonis menjadi gaya hidup yang seringkali menabrak rambu-rambu dalam beragama dan bernegara, di sisi lain sekolah-sekolah yang berbasis Islām terus menjamur. Penelitian ini bertujuan untuk menganalisis perbedaan Akhlak siswa boarding school dan non boarding school di SMA Al-Ma'soem. Metode yang digunakan dalam penelitian ini yaitu metode deskriptif dengan pendekatan kuantitatif jenis rancangan komparatif dua variabel bebas, dengan desain penelitian survei berupa angket. Data diambil dengan teknik penarikan sampel berkelompok satu tahap (cluster random sampling), adapun teknik pengolahan data menggunakan analisis data deskriptif dan analisis data inferensial dengan bantuan Microsoft Excel dan Sofware SPSS 20. Berdasarkan semua dimensi Akhlak yang dijadikan penelitian, yaitu Akhlak terhadap diri sendiri, Akhlak terhadap orang tua dan keluarga, dan Akhlak terhadap sesama manusia dan masyarakat, maka hasil penelitian setelah dibandingkan dari ketiga dimensi tersebut, diketahui bahwa Akhlak siswa boarding school dan siswa non boarding school dengan menggunakan rumus Chi kuadarat diperoleh nilai sebesar 0,107. Jika dilihat pada chi kuadrat tabel taraf signifikansi 5% yaitu sebesar 5,991, maka nilai chi kuadrat pada penelitian ini lebih kecil yaitu 0,107< 5,991. Dari hasil tersebut diketahui bahwa tidak terdapat perbedaan secara signifikan Akhlak siswa boarding school dan siswa non boarding school. Kata Kunci: Komparasi, Akhlak, Boarding, non Boarding.